2011
DOI: 10.1016/j.adolescence.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cultural values and parenting practices: Longitudinal associations with Chinese adolescents’ aggression

Abstract: Interrelations among cultural values, parenting practices, and adolescent aggression were examined using longitudinal data collected from Chinese adolescents and their mothers. Adolescents’ overt and relational aggression were assessed using peer nominations at Time 1 (7th grade) and Time 2 (9th grade). Mothers reported endorsement of cultural values (collectivism and social harmony) and parenting practices (psychological control and inductive reasoning) at Time 1. While controlling for Time 1 adolescent aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Adolescents' social harmony values were assessed at Time 2 using the Social Harmony questionnaire developed for Chinese participants (Shuster et al., ). With the inclusion of two items (“social order” and “a world of peace”) adapted from Bond and Chi (), this measure consists of twelve statements assessing how much adolescents valued harmonious interpersonal relationships in their lives (e.g., “Harmonious interpersonal relationships” and “Minimization of interpersonal conflicts”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents' social harmony values were assessed at Time 2 using the Social Harmony questionnaire developed for Chinese participants (Shuster et al., ). With the inclusion of two items (“social order” and “a world of peace”) adapted from Bond and Chi (), this measure consists of twelve statements assessing how much adolescents valued harmonious interpersonal relationships in their lives (e.g., “Harmonious interpersonal relationships” and “Minimization of interpersonal conflicts”).…”
Section: Methodsmentioning
confidence: 99%
“…These items cover social harmony values expressed in different forms (e.g., valuing harmonious relationships vs. minimizing conflict) and contexts (e.g., general value vs. in family and schools). The diverse coverage of items ensures an adequate content validity (Shuster et al., ). The Cronbach's alpha for Social Harmony questionnaire was high (α = .96).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental psychological control includes inducing guilt, love withdrawal, isolation, and shaming (Barber 1996; Barber et al 2005). Numerous studies have found a positive association between parental psychological control and aggression among adolescents (Loukas et al 2005; Shuster et al 2012; Soenens et al 2008). Among 6th and 7th grade boys and girls, maternal psychological control was positively associated with social aggression for Latino boys, but not European American boys (Loukas et al 2005).…”
mentioning
confidence: 99%
“…Maternal psychological control was related to girls’ social aggression, although this relation was mediated by social evaluative anxiety. Another study of psychological control among Chinese middle and working class 7th grade boys and girls showed a positive relation between psychological control and later relational aggression (Shuster et al 2012). Mother and father psychological control was found to be associated with adolescent relational aggression for 10th through 12th grade boys and girls in Belgium (Soenens et al 2008).…”
mentioning
confidence: 99%